Dielectric/ferroelectric and phase transition properties of PLZT ceramics. Issue 1 (27th May 2016) - Ding, Z.; Luo, T.; Mo, H.; Ruan, W.; Zhao, K.; Zhou, Y.; Xu, K.; Cheng, J.; Zeng, J.; Shur, V. Ya.; Li, G.
ABSTRACT: The La doped ceramics PLZT-0.03/1-x/x (0.43 ≤ x ≤ 0.49) around morphotropic phase boundary (MPB) region were prepared by solid-state reaction. The ceramics exhibited diffused phase transition behavior, while MPB region showed the least degree of diffusion. It has been shown that distinct difference exists between poled and unpoled samples. All the samples exhibited thermal hysteresis behavior characteristic of the first order phase transition. The ferroelectric properties of the samples were also discussed.